2019
DOI: 10.1007/s13205-019-1731-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic transformation of tropical maize (Zea mays L.) inbred line with a phytase gene from Aspergillus niger

Abstract: A full-length cDNA of phyA gene of Aspergillus niger, encoding phytase enzyme, was cloned and expressed in E. coli BL21 cells and assayed for its activity. The phyA cDNA consisted of 1404 bp, which encoded 467 amino acid residues. The phytase activity of purified phytase was 826.33 U/mL. The phyA gene under the control of endosperm-specific promoters was transformed into an Indian maize inbred line, UMI29, using particle bombardment-mediated transformation method to generate transgenic maize plants over-expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
0
3
0
1
Order By: Relevance
“…The maize lpa1-1 and lpa2-1 lines, which contain the LPA-1 (Low Phytic Acid containing Gene.) gene, act as coding proteins of multidrug resistance protein (MRP) ATP-binding cassette (ABC) transporters, which might play a role in the phytic acid accumulation and transport rather than biosynthesis in maize [ 1 , 2 , 40 ] and produce 60% less phytic acid in seed [ 66 , 67 ]. But this type of seed shows a 23% and 30% reduction in seed dry weight and germination [ 31 , 66 ].…”
Section: Regulation and Deposition Of Iron And Zinc In Maize Endospermmentioning
confidence: 99%
See 1 more Smart Citation
“…The maize lpa1-1 and lpa2-1 lines, which contain the LPA-1 (Low Phytic Acid containing Gene.) gene, act as coding proteins of multidrug resistance protein (MRP) ATP-binding cassette (ABC) transporters, which might play a role in the phytic acid accumulation and transport rather than biosynthesis in maize [ 1 , 2 , 40 ] and produce 60% less phytic acid in seed [ 66 , 67 ]. But this type of seed shows a 23% and 30% reduction in seed dry weight and germination [ 31 , 66 ].…”
Section: Regulation and Deposition Of Iron And Zinc In Maize Endospermmentioning
confidence: 99%
“… S.N. Type of phytase gene and source Promoter Signal Sequence Phytase activity Reference 1 Phys- A. niger Rice glutelin-1 seed-specific promoter Murine immunoglobulin leader peptide sequence 2,900 U/kg [ 17 ] 2 , Phy2A- A. niger Embryo-specific globulin- 1 (Glb) promoter Synthetic barley α- amylase signal peptide sequence 2,200 U/kg [ 85 , 93 ] 3 PhyA- A. niger Endosperm-specific promoter Murine immunoglobulin leader peptide sequence 20.67 U/kg [ 67 , 94 ] 4 appA- E. coli a-amylase gene ( aAmy8 ) in rice α ​ Amy8 ​signal peptide sequence in rice. 16,500 FTU/kg in Maize and 2,500 ​U/kg in Rice.…”
Section: Regulation and Deposition Of Iron And Zinc In Maize Endospermmentioning
confidence: 99%
“…UU., Australia, Colombia, México, Japón, Canadá, Taiwán y Nueva Zelanda (Garg et al, 2018). El hierro en el maíz se ha incrementado silenciando la expresión del transportador de unión al adenosín trifosfato [ATP] y mediante la expresión de la ferritina de soya y la fitasa por Aspergillus niger (Geetha et al, 2019).…”
Section: Cereales Transgénicosunclassified
“…Several researches have shown the reduction in phytic acid content of seeds following the expression of fungal phytases by plants, for example, wheat (reduction around 12-76%) [81] and Brassica napus (mutants showed an accumulation of 20.6-46.9% more phosphorous compared with the wild type when phytic acid was employed as phosphate source) [82]. Geeta et al [83] showed that seeds of Zea mays expressing an A. niger phytase had 0.6-to 5-fold more inorganic phosphorous content than the non-expressing ones.…”
Section: Filamentous Fungi Phytases Are Expressed By Yeast Plant Anmentioning
confidence: 99%